Comparative Study of Autonomous and Centralist Government Systems in the Context of Public Administration - Latief, Aswan (Generasi Sains Indonesia, 2024)
This study conducts a comparative evaluation of self-reliant and centralist authorities’ structures inside the framework of public management, that specialize in governance systems, selection-making methods, and citizen satisfaction. The method includes descriptive statistics, paired-samples t-exams, multiple regression evaluation, ANCOVA, and Pearson correlational analyses. Key findings monitor good sized variations in citizen pleasure and choice-making effectiveness between autonomous and centralist systems, with residents in independent systems reporting better pride stages. Policy interventions also caused amazing increases in pride across each structure. Regression analysis highlights the role of governance structure and carrier pleasant as giant predictors of citizen pleasure. Correlational analyses further emphasize the wonderful relationships between citizen satisfaction, service great, and accessibility. This study contributes insights into effective governance fashions and informs policymaking for more suitable public provider shipping.